220k views
4 votes
Can someone please help I’ve been stuck for over 20 minutes

Can someone please help I’ve been stuck for over 20 minutes-example-1
User Robnick
by
5.1k points

1 Answer

2 votes

To solve this problem, we will use the following properties of exponents:


\begin{gathered} (a^n)^m=a^(n* m), \\ a^na^m=a^(n+m), \\ (ab)^n=a^nb^n. \end{gathered}

Using the first and last properties, we get:


((3x^(-2))^(-2))/((-3x^(-3))(-(1)/(3)x^2)^3)=(3^(-2)x^(-2*-2))/(-3x^(-3)(-(1)/(3))^3x^(2*3)).

Simplifying the above result, we get:


(3^(-2)x^4)/(-3x^(-3)(-(1)/(3^3))x^6).

Using the second property and simplifying we get:


(x^4)/(-3^3(-(1)/(3^3))x^(-3)x^6)=(x^4)/(x^(-3+6))=(x^4)/(x^3)=x.

Answer:


x.

User Rixmit
by
5.3k points